Estágio supervisionado obrigatório osteodistrofia hipertrófica em cão (Canis lupus familiaris): relato de caso - Lima, Bruna Thayná Torres (Universidade Federal Rural do Semi-Árido, 2021)
The Mandatory Supervised Internship (ESO) aims to make the student put into practice all the theoretical knowledge and what was seen in the classroom, thus providing a previous experience before the student begins to exercise the profession. With this, it was aimed in this work to report a case that was followed in the routine of the Medical Clinic of Small Animals in the Veterinary Hospital Dix-Huit Rosado Maia of the Federal Rural University of the Semi-Arid, of a dog, male, of the breed Rottweiler of six months of age, weighing 21kg. The animal presented a history of claudication and pain in the pelvic limbs, besides also showing difficulties when standing up. With the help of radiographic exams, the diagnosis of hypertrophic osteodystrophy was reached. As treatment it was used an association of gabapentin by oral route during 20 days and tramadol hydrochloride by oral route during 7 days. After the treatment the dog presented clinical improvement and new radiographies were made that proved a very considerable and spontaneous remission of the disease.
Keywords: Osteodistrofia hipertrófica; Canino; Idiopática; CIENCIAS AGRARIAS::MEDICINA VETERINARIA